The Under-Appreciated Promiscuity of the Epidermal Growth Factor Receptor Family - Kennedy, Sean P.; Hastings, Jordan F.; Han, Jeremy Z. R.; Croucher, David R. (Frontiers in Cell and Developmental Biology, 2016)
Each member of the epidermal growth factor receptor (EGFR) family plays a key role in normal development, homeostasis and a variety of pathophysiological conditions, most notably in cancer. According to the prevailing dogma, these four receptor tyrosine kinases (RTKs; EGFR, ERBB2, ERBB3 and ERBB4) function exclusively through the formation of homodimers and heterodimers within the EGFR family. These combinatorial receptor interactions are known to generate increased interactome diversity and therefore influence signalling output, subcellular localization and function of the heterodimer. This molecular plasticity is also thought to play a role in the development of resistance towards targeted cancer therapies aimed at these known oncogenes. Interestingly, many studies now challenge this dogma and suggest that the potential for EGFR family receptors to interact with more distantly related RTKs is much greater than currently appreciated. Here we discuss how the promiscuity of these oncogenic receptors may lead to the formation of many unexpected receptor pairings and the significant implications for the efficiency of many targeted cancer therapies.